2004
DOI: 10.1161/01.cir.0000150392.70749.c7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality-of-Life Benefit After Percutaneous Coronary Intervention

Abstract: Background-Improving patients' quality of life is a primary indication for percutaneous coronary intervention (PCI), yet little is known about patient characteristics associated with greater quality-of-life improvement from the procedure. This study was conducted to identify patient characteristics associated with quality-of-life benefit after PCI. Methods and Results-A consecutive series of 1518 patients undergoing PCI in nonacute myocardial infarction settings were prospectively enrolled into an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 28 publications
10
121
1
5
Order By: Relevance
“…Although age was considered a mortality predictor in patients with CAD in one year 7 and a determinant of quality of life alterations 18 , the patients in the present study who were 65 years or older presented a variation that was similar to the ones younger than 65. Conaway et al 19 , taking into account the aging of the North-American population and the prevalence of CAD, carried out a study showing that patients older than 75 submitted to MRS, despite the slow physical recovery, did not present differences regarding the frequency of angina and quality of life, when compared to the younger patients.…”
Section: Variation Of the Saq-quality Of Life Scores In Relation To Tmentioning
confidence: 54%
“…Although age was considered a mortality predictor in patients with CAD in one year 7 and a determinant of quality of life alterations 18 , the patients in the present study who were 65 years or older presented a variation that was similar to the ones younger than 65. Conaway et al 19 , taking into account the aging of the North-American population and the prevalence of CAD, carried out a study showing that patients older than 75 submitted to MRS, despite the slow physical recovery, did not present differences regarding the frequency of angina and quality of life, when compared to the younger patients.…”
Section: Variation Of the Saq-quality Of Life Scores In Relation To Tmentioning
confidence: 54%
“…Indeed, recent studies have found substantial regional differences in post-PCI mortality across Canada, suggesting that there is an important opportunity to improve the quality of care and outcomes of PCI in all regions (6). Other data have also confirmed that substantial regional disparities exist in the utilization of cardiac invasive procedures (7)(8)(9).…”
mentioning
confidence: 80%
“…Despite this, CCS angina class has been shown to be linearly associated with increasing rates of percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG), as well as all-cause mortality and nonfatal MI. [10][11][12] Revascularization has demonstrable mortality benefits in certain defined subsets of patients with coronary artery disease (e.g., left main, triple-vessel with compromised ventricular function). However, perhaps the major objective in most patients undergoing revascularization has been the relief of angina and improvement in quality of life.…”
Section: Discussionmentioning
confidence: 99%